CONSUMER LEGAL PROTECTION ON FOOD PRODUCTS THAT DO NOT INCLUDE EXPIRED LABELS RELATED TO LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION - Noviriska (Awang Long Law Review, 2022)
The basic right of consumers related to food that does not include the expired label is the right to obtain safety. The right to security and safety is intended to ensure the safety and security of consumers in the use of goods or services obtained so that consumers can avoid losses (physical and psychological) when consuming a product, especially food products. The research that will be discussed is related to how the implementation of consumer protection against the circulation of food products that do not include an expiration date label is carried out by the YLBKI Non-Governmental Consumer Protection Agency. This research is a normative juridical law research, which is a study of norms or laws between statutory regulations and other related regulations. The results of the study show that there are many violations of consumer rights, especially violations of the right to obtain clear and honest information about the state of a product, this occurs because of consumer habits that are less careful in determining the goods used or consumed, and business actors who do not care about production standards in accordance with applicable laws so that the violation occurs. However, to fight for the rights that have been violated, you can report to one of the authorized institutions, namely the YLBKI community self-help consumer protection agency.